The Affordances of Telecollaboration to Teach Apologies - Di Sarno-García, Sofia (International Journal of English Studies, 2024)
This study presents the results of three telecollaboration projects carried out between Spanish-speaking students and their English-speaking counterparts. The aim is to explore the affordances of telecollaboration for the development of Spanish learners’ use of apologies in English. To investigate its suitability, a control group and three experimental groups were set. Quantitative analysis of the responses to a pre- and post-test, as well as quantitative content analysis of the strategies used to apologise in role-playing tasks have been carried out. The results revealed that there is a tendency toward improvement in the three experimental groups, as opposed to the control group. In line with this, the control group used a smaller range of strategies to apologise. It is concluded that the first experimental group is the one that obtained better results than the rest.